Feelings of Being for Mobile User Experience Design - Dirin, Amir; Nieminen, Marko; Laine, Teemu H. (International Journal of Human-Computer Interaction, 2023)
Creating emotionally engaging mobile applications requires consideration of constantly evolving technology, content richness, usability, and user experience (UX). UX plays an important role in promoting long-term usage. We focused on the emotional aspects of UX design of mobile applications. In particular, we adopted the concept of feelings of being (FoB)–also known as existential feelings–in the context of mobile UX design. We presented an in-depth literature review covering 112 articles (2005–2021) on human-computer interaction, UX, mobile application development, mobile learning, and emotional engagement. Of these articles, 16 discussed FoB in the context of mobile applications. Building on the results of literature analysis and other previous research, we presented a FoB model for mobile application design comprising 13 FoB (ownership, engagement, contribution, security, trust, adjustability, enjoyment, empowerment, effectiveness, frustration, excitement, gratification, and needs fulfilment) and the hedonic and eudaimonic aspects of UX. Finally, we validated the FoB model through nine design projects, proposed design recommendations based on the model, and presented considerations on extending the model with additional elements.
Keywords: Emotional aspect; Emotional engagements; Literature reviews; Mobile application development; Mobile applications; Mobile Learning; Mobile user experiences; Technology contents; User experience design; Users' experiences